Glymphatic clearance of simulated silicon dispersion in mouse brain analyzed by laser induced breakdown spectroscopy. Issue 4 (April 2020) - Khan, Muhammad Shehzad; Kumar, Rachit; Manno, Sinai H.C.; Ahmed, Irfan; Lun Law, Alan Wing; Cruces, Raul R.; Ma, Victor; Cho, William C.; Cheng, Shuk Han; Lau, Condon
Abstract: Silicon-based devices, such as neural probes, are increasingly used as electrodes for receiving electrical signals from neural tissue. Neural probes used chronically have been known to induce inflammation and elicit an immune response. The current study detects and evaluates silicon dispersion from a concentrated source in the mouse brain using laser induced breakdown spectroscopy. Element lines for Si (I) were found at the injection site at approximately 288 nm at 3hr post-implantation, even with tissue perfusion, indicating possible infusion into neural tissue. At 24hr and 1-week post-implantation, no silicon lines were found, indicating clearance. An isolated immune response was found by CD68 macrophage response at 24hr post injection. Future studies should measure chronic silicon exposure to determine if the inflammatory response is proportional to silicon administration. The present type of protocol, coupling laser induced breakdown spectroscopy, neuroimaging, histology, immunohistochemistry, and determination of clearance could be used to investigate the glymphatic system and different tissue states such as in disease (e.g. Alzheimer's). Abstract : Neuroscience; Electrode, Silicon, Inflammation, Immune response, Probe; Biophysics; Optics; Physics; Physics methods; Toxicology.